High performance P300 speller for brain-computer interface - GUAN, Cuntai (Institutional Knowledge at Singapore Management University, 2004)
P300 speller is a communication tool with which one can input texts or commands to a computer by thought. The amplitude of the P300 evoked potential is inversely proportional to the probability of infrequent or task-related stimulus. In existing P300 spellers, rows and columns of a matrix are intensified successively and randomly, resulting in a stimulus frequency of 1/N (N is the number of rows or columns of the matrix). We propose a new paradigm to display each single character randomly and individually (therefore reducing the stimulus frequency to 1/(N*N)). On-line experiments showed that this new speller significantly improved the performance. Specifically, the new speller can reduce character classification error rate by up to 80% or double the information transfer rate compared to the existing P300 spellers. © 2004 IEEE.